Interaction of dendrimers with the immune system: An insight into cancer nanotheranostics. Issue 3 (27th January 2021) - Gao, Yue; Shen, Mingwu; Shi, Xiangyang
Abstract: The immune system is a network of defense mechanisms, made up of organs, tissues, and diversified immune cells, with the mission of detecting and attacking invading pathogens. Cancer immunotherapy, which triggers effective anticancer responses via the regulation or alteration of the immune system, has emerged as one novel powerful strategy to fight cancer in contrast to the conventional resorts including surgery, radiotherapy, and chemotherapy. With the recent rapid development of nanomedicine, more opportunities are afforded to achieve highly efficient cancer immunotherapy. Dendrimers present a category of nano‐sized macromolecules with highly‐branched three‐dimensional structure, favorable biocompatibility, and tunable surface functionality. Various kinds of functionalized dendrimers and dendrimer‐based nanohybrids have been explored in the treatment and diagnosis of cancer, and they have recently been proven to be promising in cancer immunotherapy. Herein we concisely review the interesting immunomodulatory effects of dendrimers, in particular the recent advances in dendrimer‐facilitated cancer immunotherapy and cancer immunity visualization, and clarify the possible future perspectives for the design of dendrimer‐based cancer immunotheranostics. Abstract : Dendrimers have recently been proven to be promising in immunotherapy, strongly boosting cancer nanotheranostics. Herein the authors concisely review the interesting immunomodulatory effects of dendrimers, in particular the recent advances in dendrimer‐facilitated cancer immunotherapy and cancer immunity visualization, and clarify the possible future perspectives for the design of dendrimer‐based cancer immunotheranostics.